Research Progress of Plasmonic Nanostructure-Enhanced Photovoltaic Solar Cells - Adnan Ali (2542495) (2022)
Enhancement of the electromagnetic properties of metallic nanostructures constitute an extensive research field related to plasmonics. The latter term is derived from plasmons, which are quanta corresponding to longitudinal waves that are propagating in matter by the collective motion of electrons. Plasmonics are increasingly finding wide application in sensing, microscopy, optical communications, biophotonics, and light trapping enhancement for solar energy conversion. Although the plasmonics field has relatively a short history of development, it has led to substantial advancement in enhancing the absorption of the solar spectrum and charge carrier separation efficiency. Recently, huge developments have been made in understanding the basic parameters and mechanisms governing the application of plasmonics, including the effects of nanoparticles’ size, arrangement, and geometry and how all these factors impact the dielectric field in the surrounding medium of the plasmons. This review article emphasizes recent developments, fundamentals, and fabrication techniques for plasmonic nanostructures while investigating their thermal effects and detailing light-trapping enhancement mechanisms. The mismatch effect of the front and back light grating for optimum light trapping is also discussed. Different arrangements of plasmonic nanostructures in photovoltaics for efficiency enhancement, plasmonics’ limitations, and modeling performance are also deeply explored. Other Information Published in: Nanomaterials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nano12050788